O veraneio de antigamente : Ipanema, Tristeza e os contornos de um tempo passado na zona sul de Porto Alegre (1900 1960) - Machado, Janete da Rocha (2014)
The purpose of this dissertation is to analyze the formation and development of part of the south of Porto Alegre, capital of Rio Grande do Sul, from the use of the area for leisure and vacation in the first half of the twentieth century. Considering the waters of Lake Guaiba as spaces for recreation and rest, the use of the site, along the river, and cemented unleashed social and cultural relations that culminated with the progress of the entire region. The edge of Guaiba, for a long time, was the preferred site for Porto Alegre could not move to the coast, and this led economic development, motivated by the coming of groups aimed at leisure. In this sense, will be addressed how these families, many of them of German origin, appropriated the local living and living together, transforming the region into a season of rest, summer and sociability to the riverside. Centered on documents, such as newspapers, magazines, journals, maps, architectural plans, photographs and oral testimonies, the survey also enabled the production of new and provocative questions, as well as other sights. Thus, addressing urban issues and cultural, this work aims not only an analysis of the summer living in Porto Alegre at the beginning of the last century, as well as a study on the process of urbanization of the neighborhoods bordered by the lake, including Ipanema and Tristeza